Primary blastic plasmacytoid dendritic cell neoplasm: a US population-based study - Huang, Lifang; Wang, Fan (Frontiers in Oncology, 2023)
Background: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and poorly understood hematopoietic malignancy. This study aimed to investigate the clinical characteristics and prognostic factors in patients with primary BPDCN. Methods: Patients diagnosed with primary BPDCN from 2001 to 2019 were extracted from the Surveillance, Epidemiology and End Results (SEER) database. Survival outcome was analysed with Kaplan-Meier method. Prognostic factors were evaluated based on the univariate and multivariate accelerated failure time (AFT) regression analysis. Results: A total of 340 primary BPDCN patients were included in this study. The average age was 53.7 ± 19.4 years, with 71.5% being male. The mostly affected sites were lymph nodes (31.8%). Most patients (82.1%) received chemotherapy, while 14.7% received radiation therapy. For all the patients, the 1-year, 3-year, 5-year, and 10-year overall survival (OS) were 68.7%, 49.8%, 43.9%, and 39.2%, respectively, and the corresponding disease-specific survival (DSS) were 873.6%, 56.0%, 50.2%, and 48.1%, respectively. Univariate AFT analysis showed that older age, marital status of divorced, widowed and separated at diagnosis, primary BPDCN only, treatment delay for 3-6 months and without radiation therapy were significantly associated with poor prognosis of primary BPDCN patients. But multivariate AFT analysis indicated that older age was independently associated with worse survival, while second primary malignancies (SPMs) and radiation therapy were independently associated with extended survival. Conclusions: Primary BPDCN is a rare disease with poor prognosis. Advanced age was linked independently to poorer survival, while SPMs and radiation therapy were linked independently to prolonged survival.